Impatiens lixianensis, a new species of Balsaminaceae from Sichuan, China - Yu, Sheng-Xiang; Lidén, Magnus; Han, Bao-Cai; Zhang, Xiao-Xia (Phytotaxa, 2013)
Impatiens lixianensis, a new species of Balsaminaceae from Zhegushan, Lixian, Sichuan province, China, is described and illustrated. This species is closely related to I. apsotis in having small white to greenish-white flowers, 2 lateral sepals, and 1–2-flowered short racemes, but differs by its non-crested dorsal petals, a short 2-lobed swollen spur, long-clawed lower petals, and small scale-shaped upper petals. Regarding palynological characters, the lumina of the reticulum in I. lixianensis are smaller and much more granulate than those in I. apsotis.